2019
DOI: 10.1002/jlb.ma0618-231r
|View full text |Cite
|
Sign up to set email alerts
|

CRTAM+ NK cells endowed with suppressor properties arise in leukemic bone marrow

Abstract: Due to their increasing rates of morbidity and mortality, childhood malignancies are considered a global health priority, with acute lymphoblastic leukemias (ALLs) showing the highest incidence worldwide. Control of malignant clone emergence and the subsequent normal‐leukemic hematopoietic cell out‐competition require antitumor monitoring mechanisms. Investigation of cancer surveillance innate cells may be critical to understand the mechanisms contributing in either disease progression or relapse, and to promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 73 publications
(154 reference statements)
0
11
0
Order By: Relevance
“…A recent investigation has suggested that a low NK cell production in bone marrow from patients suffering from ALL may contribute in disease progression. Moreover, an increase in the percentages of NK cells expressing class I restricted T-cell associated molecule (CRTAM) may be also associated with suppressor properties favoring malignant progression [21].…”
Section: Introductionmentioning
confidence: 99%
“…A recent investigation has suggested that a low NK cell production in bone marrow from patients suffering from ALL may contribute in disease progression. Moreover, an increase in the percentages of NK cells expressing class I restricted T-cell associated molecule (CRTAM) may be also associated with suppressor properties favoring malignant progression [21].…”
Section: Introductionmentioning
confidence: 99%
“…The cell-mediated immunity is activated when a specific CTL is stimulated to initiate the lysis of pathogens, infected cells, and tumor cells; thus, this protects the body against infection and tumor growth, spreading, and metastasis ( 31 ). To prevent tumor emergence, the immune system eliminates oncogenic viral infections, induces the inflammatory microenvironment, and destroys malignant cells ( 32 , 33 ). Although tumor cells are self in origin, they differ from their normal counterparts in their biochemical and antigenic characteristics and biological behavior.…”
Section: Immune System and Tumor Evasionmentioning
confidence: 99%
“…Tumor-specific CD8+ and CD4+ T cells infiltrate the tumor site after the recognition of tumor-specific or tumor-associated antigens through HLA class I and class II molecules, respectively, which facilitate the immune mechanisms in synergy with B cells. Cancer cells that are not eradicated during the elimination phase remain in dormancy or equilibrium ( Figure 1 ) ( 33 , 43 ).…”
Section: Immune System and Tumor Evasionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysregulated ILC responses are also linked to a variety of autoimmune, fibrotic and rheumatoid diseases [81], making defining factors that direct ILC tissue-reparative vs proinflammatory programmes a major focus of ILC research. Complicating our understanding of ILCs further, several 'regulatory' populations of ILCs have been described, including regulatory NKlike cells that have cytokine profiles distinct from those of conventional NK cells [82][83][84], ILCregs which produce IL-10 and TGF-β and are defined by DNA-binding protein inhibitor ID3 expression [85], and IL-10-producing ILC2s that secrete IL-10 downstream of retinoic acid or IL-2 [85][86][87]. These regulatory ILC populations can limit autologous or allogeneic immune responses in diverse contexts [20,81,88], yet whether they have applications for type 1 diabetes is a relatively unexplored area of research.…”
Section: Ilcsmentioning
confidence: 99%